Synthesis, Characterization of some New 4-Thiazolidinone of Acenaphthoquinone - Muntaha .Y. Hayal,; Mahmood Shakir Magtoof, (University of Thi-Qar Journal of Science, 2021)
This work summarized with Synthesis of schiff's bases 1(a-c) from reaction of parent compound acenaphthoquinon with primary amines . Treating of imines compounds with thioglycolic acid was produced thiazolidinone derivatives 2 (a-c) .The structures of synthesized compounds were confirmed by using some spectroscopic analysis such as FT.IR , 1H-NMR and 13C-NMR spectral